Comparative legal analysis of the prosecutor’s activity in administrative and civil proceedings of the Republic of Kazakhstan - Alibekov А.Е.; Umargaliyev Д.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The relevance of studying the legal nature of the development, forms and legal status of the prosecutor’s participation in administrative and civil proceedings of the Republic of Kazakhstan (hereinafter referred to as the ROK) is due to the presence of practical and scientific figures seeking to abolish this institution, imitating the legal system of European countries, as well as the introduction of the Administrative Procedural Code of the ROK (hereinafter referred to as the APPC). The article draws a parallel between the participation of the prosecutor in administrative and civil proceedings, the existing differences and similarities, in particular, describes the possible forms of participation of the prosecutor in court, touches on the issue of the legal status of the prosecutor, the difference of rights and obligations from other participants in the process. The purpose of the work is to study the institution of participation of the prosecutor in administrative proceedings. The proposals put forward in science to improve the activities of the prosecutor’s office are considered. It is concluded that the APPC grants individuals and legal entities the right to appeal against the actions and inaction of not only state bodies, local self-government bodies or organizations with state participation, but also other organizations with private ownership. The authors believe that the participation of the prosecutor in administrative proceedings should not be limited only to this direction, he is also obliged to respond to other violations identified in the process. In accordance with the legal acts of the Republic of Kazakhstan, it is delimited and confirmed that, in addition to the supervisory functions of the prosecutor, there is a purpose for representing the interests of the state in court. It is proposed to unify the notification of various forms of participation of the prosecutor in the administrative process, to describe in one norm all forms of participation of the prosecutor in administrative proceedings.